Prevalence and Clinical Significance of Antiphospholipid Antibodies in Hospitalized Patients with COVID-19 Infection - Doddi, Sishir (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.